Prophylactic Theophyline reduces birth asphyxia related renal injury in term neonates - Aziz, Salma; Qudrat, Syeda Maimoona; Rani, Tanzeela; Chughtai, Qurat-ul-Ain; Aziz, Misbah; Asghar, Rai Muhammad (Journal of Rawalpindi Medical College, 2023)
BACKGROUND INTRODUCTION: Birth Asphyxia (Perinatal Asphyxia) in newborn is a condition caused by the inadequate supply of oxygen before, during, or just after birth. Kidney is the most damaged organ in asphyxiated full-term infants. Theophylline is considered to be effective as adenosine antagonist in reducing renal injury related to birth asphyxia OBJECTIVE: To determine mean serum creatinine and glomerular filtration rate in term neonates with perinatal asphyxia after prophylactic dose of theophylline as compared with that of control. MATERIALS AND METHODS: In this randomized controlled trial, a total of 60 neonates fulfilling inclusion criteria were included in study,–removed for blind review–. After taking written informed consent, all neonates were randomized into either A (Theophylline group) or B (Placebo group). Theophylline group received single dose of intravenous aminophylline (5 mg/kg, 0.25 ml/kg) while 0.25 ml/kg of normal saline was administered to placebo group over five-minute period within the first hour of presentation. Each patient was evaluated using the predesigned proforma. The 24-hour fluid intake and the urine output were recorded during the first 5 days of life. To assess the infant’s renal function, their serum creatinine, creatinine clearance (GFR) was determined on days one, three and five and compared between both groups. RESULTS: The mean age cases in Theophylline group was 10.73 ± 8.11 hours and in control group the mean age of cases was 14.33 ± 7.52 hours. In Theophylline group there were 17(56.67%) male and 13(43.33%) female cases while in control group there were 17(56.67%) male and 13(43.33%) female cases. The mean creatinine level in Theophylline group was 0.78 ± 0.29 and in control group was 1.15 ± 0.51 with statistically lower mean level in Theophylline group, p-value < 0.05. The mean Glomerular filtration rate in Theophylline group was 31.59 ± 6.35 and in control group was 21.17 ± 7.38 3with statistically lower mean Glomerular filtration rate in Theophylline group, p-value < 0.05. CONCLUSION: Through the findings of this study, the therapeutic efficacy of theophylline is confirmed in terms of maintaining serum creatinine and glomerular filtration rate. So, in future renal function can be protected by introducing theophylline and by maintaining renal function we can reduce risk of mortality. KEY WORDS: birth asphyxia, Sarnat grading system, theophylline, mean glomerular filtration rate